2021
DOI: 10.1021/acs.jpcc.1c06556
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Response of Interfacial Water at Different Lipid Monolayer Interfaces upon Interaction with Charged Gold Nanoparticles

Abstract: Understanding the interactions of nanoparticles with cell membranes is crucial for designing materials for biomedical applications. In this paper, through the combination of vibrational sum frequency generation (VSFG) and molecular dynamics simulation techniques, the spectral responses of the interfacial water molecules due to interaction of anionic gold nanoparticles (AGNPs) and cationic gold nanoparticles (CGNPs) with three differently charged model cell membranes, namely, 1,2-dipalmitoyl-sn-glycero-3-phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 102 publications
1
9
0
Order By: Relevance
“…This reduction in intensity is attributed to changes in the Stern layer configuration. 19 In this paper, we control the potential at the positive DPTAP interface by varying the concentration of negative SNPs to explore their effect on the organization of water at the interface. We have probed the interaction of a model cationic lipid, DPTAP (Figure 1a) with 28.0 ± 2.10 nm SNPs at two different pH values, i.e., pH ∼ 2 and pH ∼ 11.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This reduction in intensity is attributed to changes in the Stern layer configuration. 19 In this paper, we control the potential at the positive DPTAP interface by varying the concentration of negative SNPs to explore their effect on the organization of water at the interface. We have probed the interaction of a model cationic lipid, DPTAP (Figure 1a) with 28.0 ± 2.10 nm SNPs at two different pH values, i.e., pH ∼ 2 and pH ∼ 11.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, the investigation of the underlining mechanism of interaction of NPs with biological membranes plays a pivotal role in proposing strategies for the efficient and safe transfer of NPs into the cell membranes. Various techniques, such as surface plasmon resonance, atomic force microscopy, surface-enhanced Raman scattering, and second harmonic and sum frequency generation (SFG) spectroscopy, have been used to probe the NP–membrane interactions. Although NP–membrane interactions have received significant attention, the biochemical role of interfacial water molecules in mediating these interactions is particularly significant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…VSFG was used by Strazdaite and Roeters et al to investigate the interaction between lipid monolayers and amyloid-β protein, showing that the identity of the lipids affects the degree and type of aggregation of the protein . VSFG in conjunction with molecular dynamics simulations was used by Pandey and co-workers to study how differently charged gold nanoparticles interact with model cell membranes . They showed that the presence of the nanoparticles disrupts the structure of the water molecules in the membranes.…”
Section: Soft Interfaces and Biological Systemsmentioning
confidence: 99%
“…37 VSFG in conjunction with molecular dynamics simulations was used by Pandey and co-workers to study how differently charged gold nanoparticles interact with model cell membranes. 38 They showed that the presence of the nanoparticles disrupts the structure of the water molecules in the membranes. VSFG was used to study the structure of self-assembled monolayers, and the interaction of the monolayers with prostate cancer antigen biomarker by Raymundo-Pereira et al 39 Guo et al used VSFG to measure differences in ion binding for free and surface bound proteins.…”
Section: ■ Soft Interfaces and Biological Systemsmentioning
confidence: 99%